2012
DOI: 10.1016/j.jcma.2011.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Predictive indications of operation and mortality following renal trauma

Abstract: In conclusion, ISS ≥ 16 and RIS ≥ 4 are predictive factors for necessitating an operation, and higher injury severity (ISS ≥ 16) and lower consciousness level (GCS < 8) scores are significantly associated with mortality after renal trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0
7

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 22 publications
(14 reference statements)
0
9
0
7
Order By: Relevance
“…17.1% of their patients required emergency intervention, with grade V injury and the need for platelet transfusion significantly predicting the need for intervention. More recently, in a retrospective review of 73 patients with renal injuries, Yang et al [18], reported that an injury severity score ≥16 and a renal injury score ≥4 were predictive of the necessity of surgery. Shariat et al [19] confirmed that the AAST injury severity scale is a powerful predictor of clinical outcome in renal trauma patients.…”
Section: Discussionmentioning
confidence: 99%
“…17.1% of their patients required emergency intervention, with grade V injury and the need for platelet transfusion significantly predicting the need for intervention. More recently, in a retrospective review of 73 patients with renal injuries, Yang et al [18], reported that an injury severity score ≥16 and a renal injury score ≥4 were predictive of the necessity of surgery. Shariat et al [19] confirmed that the AAST injury severity scale is a powerful predictor of clinical outcome in renal trauma patients.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the optimal management of major blunt and penetrating renal injuries remains controversial and deserves further evaluation. 5 In this issue, Dr. Yang and colleagues 6 have done a good job of finding the factors predictive of surgery and mortality in patients with renal injury.…”
mentioning
confidence: 99%
“…5 In their article, Yang and others 6 conclude that Injury Severity Score (ISS) 16 and Renal Injury Scale (RIS) 4 are predictive factors for operation, and that higher injury severity (ISS 16) and lower conscious level (Glasgow Coma Scale (GCS) < 8) are significantly associated with mortality after renal trauma. 6 However, the authors could give more details about this scale and describe the numbers of patients in different RIS scales and their prognoses, because they want to find the predictive factors for surgery and mortality after renal trauma. In this way, the readers could get more information from the article.…”
mentioning
confidence: 99%
See 2 more Smart Citations